Propionate-oriented kitchen waste fermentation for polyhydroxyalkanoate production by mixed microbial cultures - Xiaolei Zhang; Yingxue Sun; Shaoping Luo; Song Liu; R.D. Tyagi; Hongjie Wang; Ji Li (Bioresource Technology, 2026)

Ball-milled submicron natural pyrite particles for efficient peroxysulphate activation and monochlorobenzene degradation: The role of low-molecular-weight organic acids and reduced sulfur species driving iron redox cycles - Shaofei Wen; Rui Qiu; Zhenyu Ding; Shaoping Kuang; Hongwen Sun; Peng Zhang (Journal of Environmental Chemical Engineering, 2026)

In situ sludge reduction assisted by alternating electrode-based electrochemical treatment - Xiaolei Zhang; Quanze Liu; Shaoping Luo; Yingxue Sun; Yong Li; Wenyi Dong; Patrick Drogui; Ji Li (Bioresource Technology, 2026)

Synergistic optimisation of perforated plate parameters and airflow uniformity regulation in Y-type ducting for rice seedling throwers - Guojie Jin; Yaliang Wang; Shaoping Bai; Junpeng Zhu; Haili Zhou; Liang Sun (Biosystems Engineering, 2026)

Polycyclic aromatic compounds in soils from a petrochemical-contaminated site in eastern China: Target and non-target analysis with risk assessment - Yimeng Si; Siyuan Li; Yu Wang; Ruiqi Zhang; Liman Wei; Hao Chen; Yanlong Zhang; Yiming Yao; Shaoping Kuang; Hongwen Sun (Environmental Pollution, 2026)

Synergistic inversion of maize leaf chlorophyll using multi-source remote sensing data - Shaoping Sun; Jixuan Yan; Guang Li; Zichen Guo; Wenning Wang; Qiang Li; Kejing Cheng; Xuchun Li; Jiaqin Yuan; Changbo Wu (Irrigation Science, 2026)

Seafloor imagery with an advanced imaging sonar system - Lili Zhang; Xuemei Cao; Peng Wu; Shaoping Sun; Zhiping Xu (Frontiers in Marine Science, 2026)
The mapping swath and along-track resolution can be simultaneously enhanced by using multireceiver synthetic aperture sonar (SAS). Unfortunately, the SAS parameters, including the pulse repetition frequency, SAS moving velocity, and the along-track aperture of the receiver array, are rigorously limited. Any deviation from the strict requirements could result in sampling that is not uniform. Based on the matrix inversion (MI) method, the uniform signal is recovered. The MI technique would not be able to recreate the SAS image if the redundant receivers within two subsequent pulses were extremely close or overlapped. This study discusses an innovative approach to tackle this issue. Our approach first identifies the receivers that the SAS image reconstruction algorithms exploit. Then, the approximation error caused by the range approximation is compensated for these receiver datasets. Thereafter, all receiver datasets corresponding to each pulse are stored pulse by pulse. After this operation, the omega-k algorithm is further used to reconstruct the SAS image. When the MI method works well, the proposed method can achieve high-quality images that closely match those of the matrix inversion method. More importantly, the proposed method can still work in cases where the MI method fails. The experiments further show the major superiority of our method over traditional methods.

A synbiotic combination of arabinogalactan and Bacteroides thetaiotaomicron ameliorates ulcerative colitis in mice - Shanshan Zhang; Yonggan Sun; Yuhao Li; Chunhua Chen; Shaoping Nie (Food Research International, 2026)

The prebiotic and targeted regulatory effects of konjac glucomannan on gut microbiota via multi-omics analysis - Yonggan Sun; Shanshan Zhang; Tianxiang Ouyang; Shaoping Nie (Food Hydrocolloids, 2026)

Direct carbon recovery from raw wastewater for bioenergy production by anaerobic digestion - Yingxue Sun; Ji Li; Shaoping Luo; Yinghui Liu; R.D. Tyagi; Xiaolei Zhang (Bioresource Technology, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Novel identified Faecalibacterium prausnitzii metabolites fortify the intestinal barrier: A multi-omics study - Liping Dong; Yonggan Sun; Shanshan Zhang; Tianxiang Ouyang; Xinyu Bian; Jiaqi Jiang; Wenting Su; Shaoping Nie (Food Bioscience, 2026)

Gut microbiota modulation by polysaccharide from Aloe gel: Potential prebiotic and targeted regulatory effects - Yonggan Sun; Shanshan Zhang; Shaoping Nie (Food Chemistry, 2025)

Cetyltrimethyl ammonium bromide-assisted construction of ferrous oxalate-derived graphitic carbon confined iron-based nanocluster materials for persulfate activation - Hao Sun; Wenyu Xu; Yida Wang; Chenyunuo Zhu; Jawaria Fatima; Kun-Yi Andrew Lin; Shaoping Tong (Journal of Water Process Engineering, 2025)

Insights into the impacts of diverse electron acceptors on perfluorooctanoic acid and perfluorooctane sulphonic acid removal in sediment - Huiling Sun; Liwei Zhang; Junfan Yao; Jiaqi Zhang; Tianyu Wang; Guangzhou Yu; Yan Kang; Haoqin Ma; Shaoping Kuang; Zizhang Guo; Xiaohan Jiang (Journal of Environmental Chemical Engineering, 2025)

Research Progress on bioactive peptides from animal sources: A comprehensive review - Jiteng Sun; Yanli Chen; Yue Yang; Haixia Chen; Jiayu Zhang; Shaoping Wang; Daoming Bai; Zhiqiang Sun; Jing Song; Long Dai (Food Chemistry, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Habitat use by wintering ducks and its economic impact on rice production adjacent to a nature reserve: implications for mitigating human-bird conflicts - Ningning Liu; Yanlin Cui; Yihao Fang; Shoudong Zhang; Shaoping Zang; Xuesong Feng; Wei Wu; Xuena Sun; Zhijun Ma (Biological Conservation, 2025)

Dual protection against grouper Rana-Iridovirus (GIV-R) and nervous necrosis virus (NNV) by novel GIV-R-Δ51−NNV-CP chimeric vaccine candidates - Shan Ding; Yong Li; Qianqian Sun; Zhiming Zhu; Fangzhao Yu; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Bearing capacity of post-tensioned concrete local anchorage zones under special bearing plates with multiple bearing surfaces - Chang Wu; Yanli Su; Tao Chen; Changjun Sun; Zhihong Zhang; Shaoping Meng (Engineering Structures, 2025)

Enhancing denitrifying anaerobic methane oxidation for nitrogen removal with low-temperature biochar - Wei Chong; Shaohua Wang; Jiaxin Cheng; Xue Lou; Xuebao Wan; Xiangyu Sun; Mingyang Wang; Shaoping Kuang; Hui Chen; Shuai Liu (Bioresource Technology, 2025)

Reproductive toxicity of bisphenol A and nitro-bisphenol A in male zebrafish at environmentally relevant concentrations - Chao Wang; Shuyi Zhang; Zijin Shao; Peijie Sun; Jiran Zhang; Shaoping Zhang; Jian Kong; Hong Zhi; Li Li; Mingshu Li; Jie Yu; Zhenming Liu; et al. (Science of The Total Environment, 2025)

Optimizing the activity of denitrifying anaerobic methane oxidation archaea by tailoring micronutrient compositions: A strategy for enhanced nitrate reduction - Shaohua Wang; Wei Chong; Xuebao Wan; Xiangyu Sun; Mingyang Wang; Xue Lou; Hui Chen; Shaoping Kuang; Shuai Liu (Chemical Engineering Journal, 2024)

Investigating the Effects of Perampanel on Autophagy-mediated Regulation of GluA2 and PSD95 in Epilepsy - Dan Li; Na Sun; Yingying Guo; Shaoping Huang; Chunyan Yin; Yanfeng Xiao; Weijun Ma (Molecular Neurobiology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

The structure of anthocyanins and the copigmentation by common micromolecular copigments: A review - Jiadong Wang; Yanqiao Zhao; Bing Sun; Yutong Yang; Shaoping Wang; Zirui Feng; Jianying Li (Food Research International, 2024)

Effects of four food hydrocolloids on colitis and their regulatory effect on gut microbiota - Shanshan Zhang; Yonggan Sun; Qixing Nie; Jielun Hu; Yuhao Li; Zefu Shi; Haihua Ji; Hao Zhang; Mingjiao Zhao; Chunhua Chen; Shaoping Nie (Carbohydrate Polymers, 2024)

Gut firmicutes: Relationship with dietary fiber and role in host homeostasis - Yonggan Sun; Shanshan Zhang; Qixing Nie; Huijun He; Huizi Tan; Fang Geng; Haihua Ji; Jielun Hu; Shaoping Nie (Critical Reviews in Food Science and Nutrition, 2023)

Targeted modification of gut microbiota and related metabolites via dietary fiber - Qixing Nie; Yonggan Sun; Mingzhi Li; Sheng Zuo; Chunhua Chen; Qiongni Lin; Shaoping Nie (Carbohydrate Polymers, 2023)

Iron loss and hypoxia are involved in lethal Pseudomonas plecoglossicida infections in the orange-spotted grouper Epinephelus coioides - Yujia Sun; Shaoping Weng; Binfu Xu; Chuanfu Dong; Jianguo He (Aquaculture, 2023)

Risk Assessment of Wave Over-Topping Based on Smoothed-Particle Hydrodynamics Method - Lei Wang; Li Zhang; Yanshuang Xie; Yaozhao Zhong; Yuan Sun; Zhiyuan Wang; Feng Zhang; Shaoping Shang (Journal of Marine Science and Engineering, 2022)
FETSWCM-SWAN and DualSPHysics models are used to study the storm flooding process of Dazuo Seawall in Quanzhou city, Fujian province, China. Firstly, a storm over-topping assessment method is proposed. Secondly, the water level and storm wave at the foot of Dazuo Seawall calculated by FETSWCM-SWAN during the process of Typhoon Usagi in 2013 and Typhoon Dujuan in 2015. Finally, the typical wave and storm run-up processes at Dazuo Seawall are modeled by DualSPHysics. The results show that the typical wave run-up of Dazuo Seawall is less than 2 m, but the storm wave run-up can reach 6.85 m under Usagi. The risk is high when high tide is encountered. The risk of storm flooding is classified into three grades. This risk assessment could provide decision-making support to government departments in warning against storm flooding threats.

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

Design, synthesis and biological evaluation of (E)-3-(3,4,5-trimethoxyphenyl) acrylic acid (TMCA) amide derivatives as anticonvulsant and sedative agents - Zefeng Zhao; Yajun Bai; Xufei Chen; Shaoping Wu; Xirui He; Yujun Bai; Ying Sun; Xiaohui Zheng (Medicinal Chemistry Research, 2018)

Propagation Characteristics of Blasting Stress Waves in Layered and Jointed Rock Caverns - Sheng Zeng; Shaoping Wang; Bing Sun; Qibing Liu (Geotechnical and Geological Engineering, 2018)

Polymer-Mediated Anti-solvent Crystallization of Nitrendipine: Monodispersed Spherical Crystals and Growth Mechanism - Dengning Xia; Mei Ouyang; Jian X. Wu; Yanbo Jiang; Hongyu Piao; Shaoping Sun; Li Zheng; Jukka Rantanen; Fude Cui; Mingshi Yang (Pharmaceutical Research, 2012)

The influence of macronitrogen (NO 3 − and NH 4 + ) addition with Ulva pertusa on dissolved inorganic carbon system - Naixing Zhang; Jinming Song; Conghua Cao; Rongzhu Ren; Fengcong Wu; Shaoping Zhang; Xu Sun (Acta Oceanologica Sinica, 2012)

A disjoint algorithm for seismic reliability analysis of lifeline networks - Yang Han; Shaoping Sun (Earthquake Engineering and Engineering Vibration, 2002)